An Enhanced Multi Attribute Based Trusted Attack Resistance (EMBTR) for the Secure Routing of Sensor Nodes in Wireless Sensor Network - Feroz Khan, A. B. (Wireless personal communications, 2024)
High-level security is crucial for protecting sensitive information transmitted across wireless sensor networks (WSNs). Secure routing plays a key role in preventing impersonation attacks within the network. Although numerous state-of-the-art routing models based on trusted metrics aim to enhance WSN security, challenges remain due to the network's dynamic nature. This paper introduces an enhanced multi-attribute-based trusted attack resistance (EMBTR) algorithm designed to securely manage routing using nodes' trust values. The proposed approach leverages Quality of Service (QoS) parameters such as stability rate (SR), reliability rate (RR), and elapsed time (ET) to improve network performance and combat trust-related attacks. By isolating misbehaving nodes based on their trust metrics, the algorithm establishes a reliable communication route. Comparisons with existing routing algorithms like TSRM (Trust-based Secure Routing Model) and TARF (Trust-aware Routing Framework for WSNs) demonstrate that the EMBTR algorithm effectively detects and eliminates malicious nodes, providing secure routing with higher detection rates and limited energy consumption compared to current solutions.